Development of a Digital Signature Classification Information System for Documents - Yahya Yahya; Eva Novianti; Anand Fiardhi Ramadhan (Prodi Teknologi Informasi Universitas Darma Persada, 2025)
A signature is a unique identity attached to a document, playing an essential role in verification and legal authentication. Legally, a signature represents the true authorization of the document’s owner. With the advancement of digital technology, signature pattern identification can now be performed not only manually but also with the support of computer-based systems. Recent studies in digital forensics and pattern recognition highlight the growing importance of automated signature verification to prevent falsification and ensure document integrity, especially within academic and administrative environments. This research aims to develop a web-based Digital Signature Classification Information System designed for use by administrative staff at the Faculty of Engineering, Universitas Darma Persada. The objective is to provide an accessible tool capable of distinguishing between genuine and forged digital signatures with higher accuracy and reliability. The system applies image processing techniques combined with automated classification methods to analyze signature characteristics and determine authenticity. Through this approach, the system reduces the dependency on manual inspection, which is often time-consuming and prone to human error. The results of the implementation show that the system is able to classify digital signatures effectively and can be operated easily by administrative personnel. Its deployment is expected to improve the security, validity, and accuracy of signed documents within the faculty’s administrative workflow. Overall, the system offers a practical solution for enhancing document verification processes and reducing risks associated with signature forgery